Modeling of stream/aquifer interaction during alluvial well depletion - Fox, Garey A., author; Durnford, Deanna, advisor; Sanford, William, advisor; Ramirez, Jorge, committee member; Garcia, Luis, committee member (Colorado State University. Libraries, 2003)
The conjunctive utilization of surface water and groundwater has become increasingly important as the demand for water intensifies. Water rights decisions for groundwater supplies hydraulically interacting with adjacent surface water bodies require estimation of surface water depletion due to groundwater pumping. However, stream/aquifer exchange due to groundwater extraction of tributary water is commonly analyzed using analytical solutions that oversimplify physical conditions. More complex analytical solutions have recently been developed that include the effects of a streambed layer and stream partial penetration. Such solutions have also been suggested as a way to inversely estimate aquifer parameters and the streambed hydraulic conductivity from field aquifer tests. However, numerous limitations still exist in the application of these solutions. Research is needed to develop improved analytical solutions and evaluate the significance of the more complex solutions for water rights decisions and for streambed conductivity estimation. The objectives of this research are to develop analytical models of stream/aquifer interaction during alluvial well depletion, evaluate their accuracy in the prediction of aquifer drawdown and stream depletion, and determine their ability to inversely estimate streambed conductivity. This research expands the applicability of recently proposed analytical solutions by considering finite stream width, complex aquifer flow scenarios (i.e., unconfined flow, pumping well partial penetration, delayed drainage from the unsaturated zone, well-bore storage, and well-skin effects), and unsaturated stream/aquifer exchange. Analytical solutions are derived to account for each of the stream/aquifer scenarios. Differences between the prior analytical solutions, numerical models, and the solutions developed in this research are evaluated to determine conditions when specific stream/aquifer conditions become significant. The theory developed in this research is used to improve the simulation capabilities of a standard, numerical groundwater-flow model, MODFLOW, for simulating stream/aquifer exchange. A stream/aquifer analysis test is performed at the Tamarack State Wildlife Area in eastern Colorado to investigate the inverse estimation of the streambed conductivity using the analytical solutions developed in this research.
Keywords: hydrology; civil engineering; environmental engineering; hydrologic sciences